Acute Bacterial Meningitis in Children with Fever and Fits Aged 6-59 Months Old - Syed Moeed Ahmed, Pir Jan, Saeed Zaman, Shams-Uddin Kakar, Sajid Ali Shah, Shazia Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the frequency of acute bacterial meningitis (ABM) in children presented with fever and fits aged 6-59 months old. Methodology: This cross-sectional study was done at The Department of Pediatric Medicine, Bolan Medical College/Hospital Quetta from September 2017 to February 2019. A total of 168 children, of either gender, aged between 6-59 months who presented with 1st episode of febrile seizure, and who arrived at emergency department within 12 hours of episode were included. Samples of cerebrospinal fluid (CSF) were obtained. Later, results were analyzed. Results: Of total 168 patients, 111 (66.1%) were male. The mean age was 27.19±13.80 months while the mean weight and frontooccipital circumference (FOC) was found 12.01 ± 2.05 kg and 48.68 ± 2.77 cm correspondingly. Twenty-four (14.3%) patients were diagnosed with ABM. The most common organism found among 11 positive CSF cultures was Streptococcus pneumonia in 6 (54.6%). Conclusion: Every clinician needs to thoroughly evaluate infants or young children after a simple febrile seizure. Lumber puncture can be done in every child if there is any suspicion of meningitis. Keywords: Acute bacterial meningitis, febrile seizures, fever, fits.